2020
DOI: 10.1109/access.2020.3026333
|View full text |Cite
|
Sign up to set email alerts
|

A Miniature Robotic Turtle With Target Tracking and Wireless Charging Systems Based on IPMCs

Abstract: State-of-the-art autonomous micro-robotic turtles suffer from various limitations, such as power restrictions that minimize their deployment times. In this paper, an Ionic Polymer Metal Composite (IPMC) actuator-based centimeter-level biomimetic underwater robot was designed and developed as a robotic turtle with self-charging capabilities to overcome such limitations. It could move forward and make turns driven by five IPMCs on the water. The underwater charging station was able to transmit wideband ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition to robotic fish, IPMC can also be used in other bionic underwater robots. For example, Wang et al designed a jellyfish-inspired robot by combining the IPMC with the DE actuator [150] . The DE material is used to provide power for the robot, while the deflection of the IPMC can change the direction of the robot.…”
Section: Bionic Robotsmentioning
confidence: 99%
“…In addition to robotic fish, IPMC can also be used in other bionic underwater robots. For example, Wang et al designed a jellyfish-inspired robot by combining the IPMC with the DE actuator [150] . The DE material is used to provide power for the robot, while the deflection of the IPMC can change the direction of the robot.…”
Section: Bionic Robotsmentioning
confidence: 99%
“…In 2020, Li and co‐workers designed a miniature robotic turtle with target tracking and a wireless charging system based on IPMC actuators. [ 105 ] The turtle consists of a packaged body, four pectoral fins, and a caudal fin; all the fins are made of an IPMC actuator and passive polyvinyl chloride film. By controlling the activated status of these five fins, the robotic turtle can achieve forward swimming and turning.…”
Section: Smart Material‐actuated Soft Underwater Swimming Robotsmentioning
confidence: 99%
“…EAP actuators have the potential to be a low-noise alternative. Additionally, EAP actuators can be small and able to mimic the movement of aquatic animals, which is useful in oceanographic engineering [125]. Ionic EAPs are particularly useful underwater since many types function well in aqueous solutions [126].…”
Section: Recent Advancements In the Applications Of Electroactive Polymersmentioning
confidence: 99%
“…It has been demonstrated that the stacking of IPMCs may be effective at ensuring greater actuation underwater than a single IPMC [126]. A turtle-like robot with wireless charging was made for underwater use, demonstrating the wide range of potential for the use of IPMCs underwater [125]. Ionic gel actuators and conducting polymer actuators have similar advantages in an underwater environment, although more research has been done on IPMCs [113,127].…”
Section: Recent Advancements In the Applications Of Electroactive Polymersmentioning
confidence: 99%